Life-threatening WPW syndrome without overt preexcitation - Tarcísio Medeiros de Vasconcelos, José; Galvão Filho, Silas dos Santos; Maria Vitorino Sampaio, Stela; Santos, Elizabeth de Souza; da Silva Filho, Jorge Francisco; Luis S. Correia Lima, Fernando (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
It is presented a case of a patient who had Wolff-Parkinson-White syndrome with important clinicai significance and normal 12-lead ECG. The transesophageous artificial stimulation of the heart showed presence of an accessory pathway with a very short anterograde refractory period and a last ventricular rate during atrial fibrillation. The intracardiac electrophysiologic study demonstrated a last conduction in the AV node and in a left free-wall accessory pathway, interrupted by catheter ablation. The location 01 the accessory pathway and the characteristics of the normal AV junction, covered the electrocardiographic signals 01 preexcitation. It is discussed the mechanisms 01 dissimulated preexcitation in ordinary resting ECG.